BAR Jr.: How to Tell a Tell - Borowski, Oded (The Biblical archaeology review, 1981)
When you look at a map of the Near East, you notice many place names that include as their element the word "tell." You can find names beginning with "tell" in Israel, Egypt, Syria, Lebanon, Jordan and Iraq. In Arabic and Hebrew the word "tell" means "a mound, a ruin-heap, a hill on which […]